Disseminated mycosis by Arthrocladium fulminans jeopardizing a patient with GATA2 deficiency - Egenlauf, Benjamin; Schuhmann, Maren; Giese, Thomas; Junghanss, Thomas; Stojković, Marija; Tintelnot, Kathrin; de Hoog, Sybren; Greil, Johann; Richter, Elvira; Vehresschild, Maria; Heußel, Claus Peter; Herth, Felix; et al. (Respiration, 2019)
GATA2 deficiency is characterized by monocytopenia, deficiency of dendritic cells, and a variable degree of lymphocytopenia affecting B cells and NK cells, leading to an enhanced risk of mycobacterial, viral, and fungal infections. Here we present a patient with a heterozygous intronic GATA2 mutation who acquired a fatal disseminated mycosis due to the black yeast-like fungus Arthrocladium fulminans following an infection with Mycobacterium sherrisii. This case illustrates that in patients with severe uncommon infections, immunodeficiency syndromes must be ruled out.